PENGARUH GROWTH OPPORTUNITY, FINANCIAL DISTRESS, CEO RETIREMENT TERHADAP KONSERVATISME AKUNTANSI - Hasina Tazkiya; Sulastiningsih Sulastiningsih (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
This research aims to examine and analyze the influence of growth opportunity, financial distress, and CEO retirement to the accounting conservatism at manufacturing companies listed on the Indonesia Stock Exchange. The population of the research is the manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period of 2013-2017. This research used a purposive sampling method in the selection of the sample based on predetermined criteria. Based on these criteria, obtained samples as much as 37 companies during a five years period of observation. The data used a secondary data. The data collection method used a documentation method. This research using multiple linear regression analysis and hypothesis testing using t-test, F-test and the determination of the coefficient. The results of this research indicate some of the factors that influences positively significant to accounting conservatism, such as growth opportunity and financial distress. CEO retirement has influences negatively significant to accounting conservatism.